Pelatihan Manajemen dan Pengembangan Usaha pada Koperasi SMKN 1 Rengat Kabupaten Indragiri Hulu - Firdaus A. R.; Rona Naula Oktaviani; Rahmat Setiawan; Amir Husin (ABDIMAS EKODIKSOSIORA: Jurnal Pengabdian Kepada Masyarakat Ekonomi, Pendidikan, dan Sosial Humaniora (e-ISSN: 2809-3917), 2022)
Entrepreneurship education in high schools/vocational schools is one of the government's supports for entrepreneurship development which is expected to be able to create young entrepreneurs who can create jobs in the future through strengthening MSMEs which in turn can reduce the level of hostility. However, this education is often limited to normative activities without continuous steps in everyday life. Therefore, management and business development training is needed at the SMKN 1 Rengat cooperative which is coordinated on an ongoing basis by parties who are experts in the field as part of optimizing school entrepreneurship education. The output of this community service is the Sinta 4 devotional journal which is accredited by DIKTI.